Benign and malignant cardiac masses: long-term outcomes after surgical resection. Issue 10 (3rd October 2022) - Gaisendrees, Christopher; Gerfer, Stephen; Schröder, Charlotte; Schlachtenberger, Georg; Walter, Sebastian; Ivanov, Borko; Eghbalzadeh, Kaveh; Luehr, Maximilian; Djordjevic, Ilija; Rahmanian, Parwis; Mader, Navid; Kuhn-Régnier, Ferdinand; et al.
ABSTRACT: Introduction: Cardiac tumors represent a rare and heterogenous pathologic entity, with a cumulative incidence of up to 0.02%. This study aimed to investigate one of the largest patient cohorts published for clinical presentation and long-term outcomes after surgical resection. Areas covered: Between 2009 and 2021, 183 consecutive patients underwent surgery for tumor excision in our center. Preoperative baseline characteristics, intraoperative data, and long-term survival were analyzed. The diagnosis was confirmed postoperatively by histology and Immunohistochemical investigations. Kaplan-Meier curves assessed survival, and the Cox proportional hazards model, was used to identify prognostic factors for overall survival. Results: This series included 183 consecutive patients; most (n = 169, 92.3%) were diagnosed with benign cardiac masses. The mean age of patients was 60 ± 16 years, and 48% (n = 88) were females. The largest group of tumors was myxoma (n = 98; 54%). The most common malignant tumor type was sarcoma (n = 5; 2.7%). The mean hospital stay was 11 ± 6.5 days, and all-cause mortality after ten years was 14%. Expert Opinion: Surgery represents the gold standard in treating primary cardiac tumors; in benign tumors, it is highly effective and curative, whereas, in malignant tumors, it remains associated with more prolonged survival.